2015
DOI: 10.15516/cje.v17i0.1472
|View full text |Cite
|
Sign up to set email alerts
|

Students with Disabilities and Challenges in Educational Practice/Učenici s teškoćama i izazovi obrazovne prakse

Abstract: It is well known that all educational policies promote inclusion as the major idea in a contemporary system of education. Inclusive education allows children with and without disabilities to attend the same age-appropriate classes at their local school, with additional, individually tailored support if needed. However, large equity gaps in education access and outcomes still exist between groups of children, because some marginalized groups of children experience shockingly low rates of access and learning. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…erefore, there is a need to apply a holistic approach to improve social skills [2]. Bouillet and Kudek Mirošević identified that students with special needs require exceptional support in many aspects, including learning process and adequately implemented school policies to help the students obtain good academic grades [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…erefore, there is a need to apply a holistic approach to improve social skills [2]. Bouillet and Kudek Mirošević identified that students with special needs require exceptional support in many aspects, including learning process and adequately implemented school policies to help the students obtain good academic grades [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…ere is a set of supporting factors to accelerate the academic performance of students with special needs, including emphasizing learning strategies [7], applying a holistic approach [2], inclusive schools policy [6], and teachers' rules [8,9]. However, the recent studies ignored the other essential factors, such as the role of Counseling Teachers in inclusive schools.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an examination of the prevailing literature suggests that studies on the attitudes towards accepting students with ID displayed by university members (including administration, management, and the teaching staff) are sparse. Instead, focus is on the goals and requirements of universities for enrolling such students (Hayes and Bulat, 2017;Bouillet and Mirosevic, 2015). Additionally, there is a lack of research on accepting students with ID and their status in the various universities where programs are offered (Obiozor, Onu, and Ugwoegbu, 2010;Kabuta, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Schools then become a place where children not only learn academics but also how to get along with their peers and older people. As Bouillet & Kudek-Mirošević (2015) stated that the inclusive dimension of education is lost, if we consider school as institutions which deliver only knowledge rather than student' social outcomes. For some children getting along with others and developing their social skills can be a hard task, especially for children with disabilities.…”
Section: Introductionmentioning
confidence: 99%